The Encapsulation Process of Flavonoid from Kepel Seeds (Stelechocarpus burahol) - Umi Rofiqah; Diora Ananda; Ilhamy Nurrahmah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Flavonoid contained in Kepel seeds was extracted and encapsulated using a crosslinker agent of natrium tripolyphosphate (NaTTP) aiming for protection of the flavonoid content as an antioxidant. Extraction was carried out in variation of ethanol concentration and time extraction to obtain the best extract flavonoid. Fourier Transform Infrared Spectrometry (FT-IR) method was used to determine the presence of flavonoids in the extract. Total flavonoids (TF) analysis was carried out using a UV-Vis spectrophotometer. The highest total flavonoid content was obtained in the extract with 50% ethanol concentration was 2.427% for one hour and 2.888% for two hours.